Impact of Digital Payment Systems on Societal Wellbeing - Zahid, Sheraz (Auckland University of Technology, 2021)
Digital payment systems are being increasingly adopted in both developed and developing economies. The objective of this study is to examine how the adoption of digital payment systems affects communities, societies, and countries. Using a systematic review of the literature, the various societal outcomes affected by digital payment systems are identified, as well as the pathways through which these effects occur. The study’s findings may help countries, especially those which are less well-off economically, when they are deciding whether and how much to invest in the infrastructure to support digital payment systems.
Keywords: Diigtal Payment systems; ICT; Societal well-bieng; Economic impact; Social impact; Digital payment system and political impact; Political impact; Cryptocurrrency; New payment technologies; Societal outcomes; Developing economies; Financial inclusion; Digital payment benefits; Cashless society; Cost of cash and GDP; Cash in circulation; Digital wallets; Government regulation and framework on digital payment systems; Fintech; Cashless importance in Covid-19; Econmic growth through payments